On the Historical Origin and its Mirror: In Reality of United States Trade Law - Hong, Zhao (Revue québécoise de droit international / Quebec Journal of International Law / Revista quebequense de derecho internacional, 2025)
Tracing the intellectual and theoretical development of US trade law reveals a repeated balancing and adjustment between free trade liberalism and protectionism. This evolution began in the early days of the republic when thinkers like Alexander Hamilton proposed using high tariffs and industrial support to protect nascent industries, laying the foundation for early American protectionism. As the US economy grew and its global influence expanded, free trade ideas gradually gained prominence in the late 19th and early 20th centuries. Especially after World War II, the US promoted global trade liberalization through agreements, attempting to establish free trade as the core of the international economic order. However, protectionism never completely faded. Particularly when facing external economic competition and domestic industrial pressure, the US still implements protective policies through means such as tariffs, non-tariff barriers, and Section 301. This ideological and theoretical contest is manifested in the dynamic adjustment of the US legal system. Through legal mechanisms, the US seeks a balance between open markets and national economic protection, forming a complex ’trade policy toolbox’ that both promotes global economic integration and safeguards its national interests when necessary. This evolution reflects America’s strategic thinking in response to the challenges of globalization and in maintaining its economic hegemony, providing a key historical and theoretical context for understanding the policy orientation and future direction of modern US trade law.